Prevention of Early Marriage and Optimization of Child Nutrition From the Perspective of the Qur’an - Kuswardani, Herini; Masyitoh, Dewi (CV. Rayyan Dwi Bharata, 2026)
The purpose of this study is to explain the nutritional content of fruits and vegetables mentioned in the Quran to be able to prevent malnutrition based on the results of previous studies in the health sector, and the importance of avoiding early marriage, which is one of the causes of stunting and malnutrition in babies. The library's method is reassessed using the latest research articles that are related to and support this research. The discussion is that Islam is considered to legalize early marriage to avoid adultery, but the verse An-Nisa' verse 6 means to prevent early marriage. The Quran also recommends eating fruits and vegetables to maintain nutritional fulfillment and health. Al-Baqarah verses 168 and 233, Al-Maidah: 88, Al-Anfal: 69, An-Nahl: 114, about food and the importance of breast milk